2011
DOI: 10.1089/ars.2010.3751
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: Activation of Akt Rescues Endoplasmic Reticulum Stress-Impaired Murine Cardiac Contractile Function via Glycogen Synthase Kinase-3β-Mediated Suppression of Mitochondrial Permeation Pore Opening

Abstract: Aims: The present study was designed to examine the impact of chronic Akt activation on endoplasmic reticulum (ER) stress-induced cardiac mechanical anomalies, if any, and the underlying mechanism involved. Results: Wild-type and transgenic mice with cardiac-specific overexpression of the active mutant of Akt (Myr-Akt) were subjected to the ER stress inducer tunicamycin (1 or 3 mg/kg). ER stress led to compromised echocardiographic (elevated left ventricular end-systolic diameter and reduced fractional shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 48 publications
9
67
0
Order By: Relevance
“…Importantly, inhibition of GSK-3β caused a prominent reduction in GADD153 expression with the effect more marked for the pressure overloaded hearts. This observation is consistent with the emerging role of GSK-3β in regulation of ER stress response and associated GADD153 expression including activation of protein kinase B/Akt ameliorates ER-stress-induced murine cardiac contractile dysfunction via GSK-3β-mediated suppression of MPT pore opening 42 and inhibition of GSK-3β reduces ER stress-induced C/EBP homologous protein (ie, GADD153) expression in neuronal cells. 12 A hallmark feature of IR injury is marked oxidative/nitrosative stress.…”
Section: 35supporting
confidence: 84%
“…Importantly, inhibition of GSK-3β caused a prominent reduction in GADD153 expression with the effect more marked for the pressure overloaded hearts. This observation is consistent with the emerging role of GSK-3β in regulation of ER stress response and associated GADD153 expression including activation of protein kinase B/Akt ameliorates ER-stress-induced murine cardiac contractile dysfunction via GSK-3β-mediated suppression of MPT pore opening 42 and inhibition of GSK-3β reduces ER stress-induced C/EBP homologous protein (ie, GADD153) expression in neuronal cells. 12 A hallmark feature of IR injury is marked oxidative/nitrosative stress.…”
Section: 35supporting
confidence: 84%
“…Previous studies also reported that 4-HNE triggered suppression of Akt activity (27), compromised cardiomyocytes mechanical function and protein damage (25). ER stress induction was found to promote carbonyl formation (14,17), whereas carbonyl formation was also upregulated in response to 4-HNE exposure, which was attenuated by ALDH2 overexpression (25). Taken together, the above evidence suggests that the role of ALDH2 against ER stress, at least in part, was attributed to the detoxification of 4-HNE with ALDH2.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 84%
“…However, the role of Akt signaling in regulation of ER stress is controversial. Activation of Akt was found to rescue the cardiac mechanical function defect induced by ER stress, whereas it did not affect the protein levels of ER stress markers (14,17). Recent studies demonstrated that inhibition of ER stress by intermedin was blocked by the PI3K inhibitor (29).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 98%
See 2 more Smart Citations